Fine mapping MHC associations in Graves' disease and its clinical subtypes in Han Chinese. Issue 10 (9th July 2018) - Chu, Xun; Yang, Minjun; Song, Zhen-Ju; Dong, Yan; Li, Chong; Shen, Min; Zhu, Yong-Qiang; Song, Huai-Dong; Chen, Sai-Juan; Chen, Zhu; Huang, Wei
Abstract : Background: The classical human leucocyte antigen (HLA) genes were the most important genetic determinant for Graves' disease (GD). The aim of the study was to fine map causal variants of the HLA genes. Methods: We applied imputation with a Pan-Asian HLA reference panel to thoroughly investigate themajor histocompatibility complex (MHC) associations with GD down to the amino acid level of classical HLA genes in 1468 patients with GD and 1490 controls of Han Chinese. Results: The strongest finding across the HLA genes was the association with HLA-DPβ1 position 205 (Pomnibus =2.48×10 −33 ). HLA-DPA1*02:02 was the strongest association among the classical HLA alleles, which was in perfect linkage disequilibrium with HLA-DPα1 residue Met11 (OR=1.90, Pbinary =1.76×10 −31 ). Applying stepwise conditional analysis, we identified amino acid position 205 in HLA-DPβ1, position 66 and 99 in HLA-B and position 28 in HLA-DRβ1 explain majority of the MHC association to GD risk. We further evaluated risk of two clinical subtypes of GD, namely persistent thyroid stimulating hormone receptor antibody -positive (pTRAb+) group and 'non-persistent TRAb positive' (pTRAb−) group after antithyroid drug therapy. We found that HLA-B residues Lys66-Arg69-Val76 could drive pTRAb− GD risk alone, while HLA-DPβ1 position 205, HLA-B position 69 and 199 and HLA-DRβ1 position 28 drive pTRAb+ GD risk. The risk heterogeneity between pTRAb+ and pTRAb− GD might be driven by HLA-DPα1 Met11. Conclusions: Four amino acid positions could account for the associations of MHC with GD in Han Chinese. These distinct HLA association patterns indicated the two subtypes have distinct molecular mechanisms of pathogenesis.